ANALYSIS OF QUALITY CONTROL FOR POTASSIUM TESTING AT KASIH IBU HOSPITAL LABORATORY IN SURAKARTA - S, Muhammad Ilham; Putri, Arum Kusuma; Dewi, Yulia Ratna (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Laboratory testing plays a crucial role in supporting patient diagnosis and monitoring; therefore, accurate and precise results are essential through the implementation of quality control (QC). Potassium level testing is one of the key parameters requiring robust quality control because it is closely linked to patients’ clinical conditions. This study aims to analyze the implementation of QC in potassium level testing using the EasyLyte device at the Kasih Ibu Hospital Laboratory in Surakarta. The research method used was quantitative descriptive with an observational approach using secondary data from QC results for the period from September to November 2025. Analysis was performed by calculating the mean, standard deviation (SD), coefficient of variation (CV), and evaluating the Westgard rules. The results showed that the CV values for normal and abnormal controls were within acceptable limits (≤5%), and no violations of any Westgard rules were found. This indicates that the test results have good precision and there are no deviations, either random or systematic. Overall, the analytical system is in control and the instrument performance is stable. Thus, potassium testing using the EasyLyte instrument meets quality requirements and is suitable for use in laboratory services, while still requiring QC monitoring as well as routine maintenance and calibration.